A New Method for Optimal Reconstruction of Radial Distribution Network; Case Study in KERMAN - Mahdi Mozaffari Legha (Journal of Global Pharma Technology, 2017)
The availability of an adequate amount of electricity and its utilization is essential for the growth and development of the country. Development of distribution systems result in higher system losses and poor voltage regulation. Consequently, an efficient and effective distribution system has become more urgent and important. In medium voltage electrical distribution networks, reformed the loss reduction is very important and certainly in line with this, system engineering issue and use of proper equipment, a good work has been done. Hence proper selection of conductors in the distribution system is important as it determines the current density and the resistance of the line. In this paper examines the use of different evolutionary algorithm, imperialist competitive algorithm (ICA) to optimal branch optimization Reconstruction of aging of overhead conductors in t radial distribution systems with objective function to reduce the sum of capital cost and power loss cost and voltage deviation. This algorithm is easy to programming and needs no approximation of actual condition. The proposed method can be applied for optimal planning of radial electric distribution systems. Effectiveness of the proposed method is shown by case study in a radial network.Keyword: Optimization, Reconstruction, aging of overhead conductors, Imperialism Competitive Algorithm (ICA), Radial Distribution Networks, back/forward sweep, Voltage profile, Loss Reduction.